HUBUNGAN PENGETAHUAN, POLA MAKAN DENGAN KADAR ASAM URAT PADA PASIEN DIABETES MELITUS DI PUSKESMAS JOHAN PAHLAWAN - wulandari, Desti; Rinawati; Mulyani, Itza; Eka Putri, Suci (Universitas Cokroaminoto Palopo, 2024)
This research is a quantitative research with a cross sectional approach carried out at the Johan Pahlawan Community Health Center with a sample size of 86 respondents. A total of 26 (30.2%) respondents with more or less knowledge had high cholesterol, while 9 respondents (10.5%) with normal cholesterol levels had good knowledge. This value means Ha is accepted and H0 is rejected. As many as 33 (38.4%) respondents with more or less eating patterns had high cholesterol, while 10 respondents (11.6%) with normal cholesterol levels had good eating patterns. This value means Ha is accepted and H0 is rejected. Shows a significant relationship between the level of knowledge and cholesterol levels. The results of the Chi-Square statistical test show a p-value of 0.010 (α < 0.05). shows a significant relationship between diet and cholesterol levels, with a p-value of 0.012 (α < 0.05).